2017
DOI: 10.1186/s40589-017-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing China’s recent capital outflows: policy challenges and implications

Abstract: China has experienced a dramatic swing from net capital inflows to large net outflows in recent years. Using balance of payments data, an analysis of the underlying factors that drove China's recent capital outflows since mid-2014 were (1) corporates adjusting their balance sheets to reduce foreign exchange exposure or to unwind "carry trade"; (2) Chinese corporate and households seeking to diversify assets offshore; (3) Renminbi internationalization push, which facilitated capital outflows and capital flight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…As an exception, Voss et al (2010) find that China’s inefficient banking system has pushed disadvantaged smaller firms to invest abroad when seeking to obtain external funding. Only recently, the literature began positing that Chinese OFDI could be a way to escape from unfavorable domestic conditions (Buckley et al , 2018; Chan, 2017; Cheung et al , 2016; Gunter, 2017). Buckley et al (2018) identified this topic as a critical area for future research and emphasized that “the use of FDI as a cover for capital flight is growing” (p8), e.g.…”
Section: Literature Methods and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an exception, Voss et al (2010) find that China’s inefficient banking system has pushed disadvantaged smaller firms to invest abroad when seeking to obtain external funding. Only recently, the literature began positing that Chinese OFDI could be a way to escape from unfavorable domestic conditions (Buckley et al , 2018; Chan, 2017; Cheung et al , 2016; Gunter, 2017). Buckley et al (2018) identified this topic as a critical area for future research and emphasized that “the use of FDI as a cover for capital flight is growing” (p8), e.g.…”
Section: Literature Methods and Hypothesesmentioning
confidence: 99%
“…As a new risk measure that has increasingly drawn scholarly attention since the 2008 financial crisis, systemic risk represents the extreme downside risk associated with economic collapse (Kaufman and Scott, 2003; Schwarcz, 2008; Acharya et al , 2017; Zhou et al , 2020). It excludes upside volatility and, as such, is more appropriate risk measure than systematic or idiosyncratic risk for assessing the role of risk in international diversification (Buckley et al , 2018; Chan, 2017; Cheung et al , 2016; Gunter, 2017). The measure of systemic risk used in our analysis calculates the expected decrease in an industry’s value when the stock market index falls into the left 5% tail and thus shows an industry’s risk due to extreme market collapse, while the traditional measures of risk, systematic risk and idiosyncratic risk, measure only an industry’s overall volatility due to market and firm-specific risk sources respectively.…”
Section: Introductionmentioning
confidence: 99%
“…After relocating labor-intensive manufacturing production to other countries, the services, such as shipping, insurance, wholesale facilities, and after-sales services, became important OFDI that supported Chinese manufacturing firms' production and sales in host countries (Xu, 2011). Concerns about a weaker RMB coupled with a slower rate of return on domestic investment have led to the repatriation of OFDI profits as well (Chan, 2017). The overseas investment helped to diversify Chinese firms' markets and improve their financial position (Tan, 2013).…”
Section: China's Asean Choicementioning
confidence: 99%
“…The potential short-term cross borders capital outflow could be tempered by the capital control policy of China. A lot of literature explores the effectiveness of China's capital control [15][16][17]. A model, known as "the Mundell-Fleming trilemma", describes why capital control plays an important role in regulating exchange rates while keeping the independent monetary policy.…”
Section: China's Response To Fed Rate Hikesmentioning
confidence: 99%